2016
DOI: 10.1007/s00330-016-4352-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carcinoembryonic antigen (CEA) density as a prognostic factor for percutaneous ablation of pulmonary colorectal metastases

Abstract: • CEA density is an independent prognostic factor for colorectal pulmonary metastases. • A lower CEA density is associated with better overall survival. • CEA may play a functional role in tumour progression. • High CEA density is associated with smaller tumours. • Interval between pulmonary ablation and primary colorectal carcinoma is a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Despite many published studies that have demonstrated the prognostic impact of CEA among CRC patients, no agreement concerning the cutoff values has been established[20-24]. Moreover, Tong et al[12] found that postoperative tissue CEA is significantly associated with the prognosis of CRC, and Huo et al[13] illustrated that serum CEA density was an independent prognostic factor in patients with colorectal pulmonary metastasis. CEA, as a classic tumor marker, is used to evaluate the biological activity of malignancies, but biological activity will also be affected by tumor quantity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many published studies that have demonstrated the prognostic impact of CEA among CRC patients, no agreement concerning the cutoff values has been established[20-24]. Moreover, Tong et al[12] found that postoperative tissue CEA is significantly associated with the prognosis of CRC, and Huo et al[13] illustrated that serum CEA density was an independent prognostic factor in patients with colorectal pulmonary metastasis. CEA, as a classic tumor marker, is used to evaluate the biological activity of malignancies, but biological activity will also be affected by tumor quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that detecting the CEA produced and secreted by all tumor cells is not realistic, using the ratio of CEA to tumor size may somehow reflect the ability of tumor cells to secrete CEA. Another research group demonstrated that CEA density is a prognostic factor for percutaneous ablation of pulmonary colorectal metastases[13]. Using tumor size to adjust and improve the prognostic value of tumor marker is not uncommon, such as prostate specific antigen density and tumor-infiltrating CD8+ T-cell density[14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the levels of CEA and AFP in the plasma remain valuable biomarkers for evaluating CRC progression ( 23 25 ), the potential association between ASPP mRNA expression and CEA or AFP concentrations in the samples was examined in the early and advanced groups ( Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that absolute serum CEA level is a strong independent prognostic factor for patients with advanced CRC and CRPC . In addition, Nakagoe et al identified that a high CEA concentration within tumor tissue was an independent poor prognostic factor, while Huo et al found serum CEA tumor density to be an independent prognostic factor in patients with colorectal pulmonary metastasis undergoing percutaneous ablation. These findings indicate that tumor marker levels may depict tumor biology rather than being simply a function of tumor quantity, with more aggressive tumours emitting higher quantities of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor marker levels, such as CEA, may indicate tumor biological activity, rather than being simply a function of tumor quantity. Recent data indicates that serum CEA tumor density is an independent prognostic factor in patients with colorectal pulmonary metastasis undergoing percutaneous ablation, indicating that aggressive tumors emit higher quantities of circulating, measurable tumor markers.…”
Section: Introductionmentioning
confidence: 99%